Effect of Alum, Iron Sulfate, and Quicklime Mordants on the Ecoprint Quality of Loropetalum chinense Leaves on Satin Fabric Using the Hapazome Technique - Revi Savitri; Adriani Adriani (Ekspresi Seni : Jurnal Ilmu Pengetahuan dan Karya Seni, 2025)
This study was motivated by the use of pitaloka leaves (Loropetalum chinense) to create patterns using the hapazome technique with the help of mordants and fixatives. The purpose of this study is to describe the color names, clarity of motif shapes, and washfastness of the results of the hapazome ecoprint technique using pitaloka leaves on Roberto fabric. This study is an experimental study with Roberto fabric as the research object, which was given motifs using the ecoprint technique. The type of data in this study was primary data sourced from questionnaires filled out by 15 panelists. The data analysis technique in this study used ANOVA and was analyzed with the Friedman K-Related Sample test. Ecoprint results without mordant, alum mordant, tunjung, and pure lime produced a variety of colors. The results of the clarity of the ecoprint motif using pitaloka leaves (Loropetalum chinense) on Roberto fabric without mordant showed that 67% of panelists stated that it was clear, with alum mordant 53% of panelists stated that it was very clear, with tunjung mordant 40% stated that it was clear, and with pure lime mordant 40% stated that it was clear. The results of the Friedman k-related test for color fastness to washing using alum mordant were 0.001 < 0.05, meaning there was a significant difference, using alum mordant was 0.022 < 0.05, meaning there was a significant difference, and using pure lime mordant was 0.234 > 0.05, meaning there was no significant difference from the ecoprint results of pitaloka leaves.